Competency of Shariah Auditors in Islamic Banking Institutions: ‎Challenges and Pragmatic Solution - SHAFIQUE, ESHAA; DUR-E-AYMEN; SHAHZAD, MUHAMMAD ASGHAR (International Journal of Islamic Economics and Governance, 2022)
Islamic banking is a Shariah-compliant alternative to the conventional banking system. All operations, products, and businesses adhere to Shariah guidelines in Islamic banking. The responsibility of Shariah auditors is to ensure that all the operations of the Islamic bank align with Shariah rules and principles. The job of Shariah auditors is very sensitive compared to any other audit because the findings of Shariah auditors serve as the basis for the Shariah board to form an opinion about the Shariah compliance environment of Islamic banks. The study will focus on the challenges of the competence of Shariah auditors in the Islamic finance industry and will draw conclusions using qualitative and quantitative methods. The paper will be divided into two parts: in the first part, researchers will collect data using survey methods and analyze it; in the second part of the study, interviews with experts will be included. The paper will be helpful for practitioners, policymakers, and specifically for the State Bank of Pakistan to enhance the Shariah compliance environment in the Islamic Finance Industry.